Virginia Woolf - Harris, Alexandra, 1981- (New York : Thames & Hudson, 2011)
Discusses the life and work of the twentieth-century English author, Virginia Woolf.
Victorians : 1882-1895 -- Getting through : 1896-1904 -- Setting up : 1905-1915 -- Making a mark : 1916-1922 -- 'Drawn on and on' : 1923-1925 -- 'This is it' : 1925-1927 -- A writer's holiday : 1927-1928 -- Voices : 1929-1932 -- The argument of art : 1932-1938 -- Sussex : 1938-1941.
Includes bibliographical references (pages 172-183) and index.
Keywords: Woolf, Virginia, -- 1882-1941 -- Biography; Woolf, Virginia, -- 1882-1941.; Woolf, Virginia -- 1882-1941; Woolf, Virginia; Woolf, Virginia, -- 1882-1941.; Woolf, Virginia; Woolf, Virginia; Women novelists, English -- 20th century -- Biography; Novelists, English -- 20th century -- Biography; Novelists, English; Women novelists, English; English novelists -- Biography; 1900-1999; Biographies; Biography; Biographies